1990
DOI: 10.1007/bf00314624
|View full text |Cite
|
Sign up to set email alerts
|

Polyneuropathy associated with chronic hypoxaemia: prevalence in patients with chronic obstructive pulmonary disease

Abstract: The prevalence of clinical and electrophysiological signs of peripheral nerve disease was evaluated in 151 patients with chronic obstructive pulmonary disease. Patients with concomitant disorders affecting the peripheral nervous system were excluded. Thirty patients had clinical signs of a mild sensorimotor and distal neuropathy and 13 additional patients had only electrophysiological abnormalities. The rate and the severity of the neuropathy correlated with the severity of chronic hypoxaemia. Three out of 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 11 publications
1
36
0
Order By: Relevance
“…In turn, this could potentially amplify the smoke-dependent abnormalities in cerebrovascular dynamics. While a definite neuropathy has been described in severe COPD [37], the present findings of an immediate modification with breathing manoeuvres suggest that these abnormalities resulted from a still functional (and reversible) disturbance in patients with limited clinical involvement. The clinical implications of an alteration in the autonomic nervous system and cerebrovascular dynamics are clear when considering the recently reported high sensitivity of the solitary tract nucleus to changes in blood flow [38].…”
Section: Autonomic Disturbances In Copd Patientsmentioning
confidence: 39%
“…In turn, this could potentially amplify the smoke-dependent abnormalities in cerebrovascular dynamics. While a definite neuropathy has been described in severe COPD [37], the present findings of an immediate modification with breathing manoeuvres suggest that these abnormalities resulted from a still functional (and reversible) disturbance in patients with limited clinical involvement. The clinical implications of an alteration in the autonomic nervous system and cerebrovascular dynamics are clear when considering the recently reported high sensitivity of the solitary tract nucleus to changes in blood flow [38].…”
Section: Autonomic Disturbances In Copd Patientsmentioning
confidence: 39%
“…Appenzeller et al (1968) firstly reported Wallerian degeneration and demyelinization of the peripheral nerves in patients with COPD (Pfeiffer et al 1990). Afterwards, the role of polyneuropathy (PNP) in COPD has been shown in various studies (Ozge & Atis¸2001;Agrawal et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, the role of polyneuropathy (PNP) in COPD has been shown in various studies (Ozge & Atis¸2001;Agrawal et al 2007). Hypoxaemia has been proposed as the major factor for the development of polyneuropathy (Pfeiffer et al 1990;Ozge & Atis2 001;Ozge et al 2005). Hypoxaemia may cause neuropathy by its direct effect on the nerve fibres or by increasing the impact of neurotoxic factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxic neuropathy expressed by peripheral paraesthesia, reduced peripheral sensory nerve conduction and axonal neuropathy is well known in patients with COPD [19, 20, 21, 22]. Symptoms such as postural fainting, diarrhoea, loss of urinary control, erectile impotence and reduced sweating, common in COPD, may be due to autonomic neuropathy [23, 24, 25, 26].…”
Section: Introductionmentioning
confidence: 99%